Three‐stage doherty amplifier with uneven input splitter. Issue 6 (27th March 2013) - Seo, M.; Song, M.; Gu, J.; Kim, H.; Ham, J.; Park, C.; Yang, Youngoo
Abstract This article presents a new high‐efficiency three‐stage Doherty power amplifier (DPA) using a simple uneven power splitter. The proposed three‐way uneven power splitter, which was designed based on a multiway Wilkinson power divider, was applied to the three‐stage DPA. Also, the proposed structure is much simpler and uses fewer lumped components than the conventional one. Using the uneven input splitter, each individual amplifier in the DPA has an appropriate input power level. It results in a proper load modulation of the three‐stage Doherty amplifier. The proposed three‐stage DPA has been implemented for the E‐UTRA‐13 band of from 746 to 756 MHz. For the LTE‐frequency‐division duplexing release 9 downlink signal with a peak‐to‐average power ratio of 10 dB and a signal bandwidth of 5 MHz, a high power‐added efficiency of 42.3% and an adjacent channel leakage power ratio of −37 dBc at an offset of 2.7 MHz were experimentally achieved at an average output power of 30 dBm. © 2013 Wiley Periodicals, Inc. Microwave Opt Technol Lett 55:1405–1409, 2013; View this article online at wileyonlinelibrary.com. DOI 10.1002/mop.27581